Optimasi Penjualan UMKM Jamu NGEJAMU ANG KEKINIAN dengan Pembuatan Box Cooler Portable Berbasis Mikrokontroller - Miftakhul Huda; Septriandi Wirayoga; Guntur Yanuar Astono; Isac Ilham Akbar Habibi; Azam Muzakhim Imammuddin (Pusat Riset dan Inovasi Nasional, 2025)
Traditional herbal medicine MSMEs face challenges in increasing the appeal of their products among the younger generation who prefer fresh and modern drinks. To overcome this, innovation in the presentation of herbal medicine is needed to make it more practical, hygienic and attractive. One solution is the manufacture of a microcontroller-based portable box cooler that can maintain the freshness of herbal medicine at an optimal temperature. This box cooler is equipped with an automatic cooling system controlled by a microcontroller, ensuring the jamu stays fresh and high quality for a longer period of time. A temperature sensor monitors and adjusts the cooling conditions as needed, so that the herbs remain at their best when served. In addition, the automatic dispenser system helps regulate the volume of herbs dispensed precisely, reducing wastage and maintaining flavour consistency. With its portable and efficient design, this box cooler is perfect for use in various locations such as bazaars, cafes, offices, or community events. This innovation not only improves the efficiency and competitiveness of MSMEs, but also reinforces the image of jamu as a modern and contemporary healthy drink, making it more attractive to young consumers.